Penanaman Nilai-Nilai Karakter Cinta Tanah Air Melalui Kegiatan Ekstrakurikuler Berbasis Kearifan Lokal Reog Ponorogo di SMA 3 JEMBER - Dewi, Putri Rosdiana; Damayanti, Risqia Putri; Nurhayati, Alfisyah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research is motivated by the problem of degradation of character values ​​that is currently occurring, the impact of which has an impact on decreasing the value of one's love for one's homeland. The fading character of love for one's country, one of which is proven by the existence of students who are currently more than foreign cultures entering this nation, such as music groups from Europe, Korea (K-pop), like television dramas (K-drama). , movie, K-mode. The aim of this research is to determine the cultivation of the values ​​of love for the country through extracurricular activities based on local wisdom in Reog Ponorogo at SMA 3 Jember. This research uses qualitative research with a case study type of research. The data collection techniques used are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions or verification. These results show that there are character values ​​of love for the country contained in the reog extracurricular at SMA 3 Jember, including the character of heroism, heroism, tough personality, good morals, discipline, love of local arts and preserving local culture.